2020
DOI: 10.3389/fimmu.2020.567406
|View full text |Cite|
|
Sign up to set email alerts
|

IL-7 During Antigenic Stimulation Using Allogeneic Dendritic Cells Promotes Expansion of CD45RA-CD62L+CD4+ Invariant NKT Cells With Th-2 Biased Cytokine Production Profile

Abstract: Invariant natural killer T (iNKT) cells are innate-like T lymphocytes cells that recognize glycolipid antigens associated with CD1d, non-classical antigen presenting proteins. They can drive either pro-inflammatory (Th-1) or anti-inflammatory (Th-2) immune microenvironment through the production of both Th-1 and Th-2 type cytokines upon activation, thus play a vital role in cancer, infection, and autoimmune diseases. Adoptive cell therapy using ex vivo expanded iNKT cells is a promising approach to enhance ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Comparing the Desensitized and Anaphylactic groups, 5,596 unique DMPRs were found, from which several upmethylated DMPRs could influence genes linked to DC activation. Among them, we found toll-like receptors ( Tlr4 , Tlr3 , Tlr8 , Tlr5 ), and other genes linked to its function including Cd180 and Tirap ( 54 ); genes involved in IL-2 production from DC like Cd247 , Irf4 , and Pde4b ( 55 ); and other cytokines such as Th1 promoting Il27 ( 56 ), Th2 enhancing Il7 ( 57 ), and pro-cytotoxic Il15 ( 58 , 59 ). Assuming a canonical relation between CpG methylation and expression, these changes would result in a reduction of DC proinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the Desensitized and Anaphylactic groups, 5,596 unique DMPRs were found, from which several upmethylated DMPRs could influence genes linked to DC activation. Among them, we found toll-like receptors ( Tlr4 , Tlr3 , Tlr8 , Tlr5 ), and other genes linked to its function including Cd180 and Tirap ( 54 ); genes involved in IL-2 production from DC like Cd247 , Irf4 , and Pde4b ( 55 ); and other cytokines such as Th1 promoting Il27 ( 56 ), Th2 enhancing Il7 ( 57 ), and pro-cytotoxic Il15 ( 58 , 59 ). Assuming a canonical relation between CpG methylation and expression, these changes would result in a reduction of DC proinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if human iNKT cells generally retain functional plasticity, it may be important to identify methods to specifically promote their regulatory functions. To this end, a recent study found that the presence of IL-7 during in vitro expansion of human iNKT cells resulted in a CD4 + population with enhanced T H2 cytokine production ( 106 ), while exposure to short chain fatty acids, palmitate, or the mTOR inhibitor rapamycin may induce a regulatory phenotype ( 27 , 37 , 107 ). Another important consideration is that iNKT immunotherapy that engages T H2 pathways would likely be contraindicated in certain inflammatory diseases, including asthma, chronic obstructive pulmonary disease, and ulcerative colitis, where T H2 cytokine production by iNKT cells has been associated with disease-exacerbating effects (reviewed in ( 108 110 )).…”
Section: Discussionmentioning
confidence: 99%
“…treatment with a combination of IL-2 and IL-21 (but not IL-2 alone) downregulated the proapoptotic protein BIM in CD62L + iNKT cells, thus protecting them from activation-induced cell death (111,112). While these studies have been conducted in mice, evidence suggests that human iNKT cells can also express CD62L (113).…”
Section: Human Inkt Cell Subsetsmentioning
confidence: 99%